Karakteristik Pasien Katarak di Rumah Sakit Ari Canti Periode Tahun 2017-2019 - Ida Bagus Arik Tahayana; Asri Lestarini; Ni Nyoman Sunariasih (Aesculapius Medical Journal, 2024)
[Characteristic of Cataract Patients at Ari Canti Hospital From 2017-2019] Cataract is an ocular condition characterized by the opacification of the eye's lens, leading to visual impairment. Cataracts are caused by the disruption of mechanism between water and electrolytes which is triggered by the denaturation of lens proteins. Cataracts represent the predominant etiology of blindness and it is estimated that around 65.2 million people in the world suffer from cataracts. Although cataract surgery has been proven to reduce blindness, cataracts are still the leading cause of blindness in developing countries due to the lack of access to medical services and eye examinations. This investigation seeks to ascertain the attributes of cataract patients in relation to age, gender, systemic comorbidities (which consists of diabetes and hypertension), cataract severity, and visual acuity within the timeframe of 2017-2019 at Ari Canti Hospital. This descriptive research takes place in Ari Canti Hospital and it’s using cross-sectional method. Samples were obtained by consecutive sampling technique and data were collected by obtaining patient medical records to provide sample characteristics. The total amount of samples gathered were 262 samples. Results concluded that cataracts are more susceptible to people aged between 70-79 years, female and those who have a history of hypertension. Most cataracts symptoms begin at the immature stage and visual acuity is mostly at UCVA >3/60. Several recommendations for this study could serve as a basis for cataract screening and management policies and might also serve as a reference for future research endeavors.